THE EMOTIONAL INFLUENCE ON YOUNG LEARNERS IN FOREIGN LANGUAGE LEARNING - Odinayeva Nilufar Lukmonovna,Jalolova Lola (International Journal of Literature and Language Studies, 2026)
This article discusses how emotions shape young learners' foreign language (FL) learning. It argues that children's progress depends not only on vocabulary, grammar, and classroom materials, but also on feelings of safety, curiosity, confidence, belonging, and willingness to take risks. Based on a literature review and pedagogical analysis, the article explains how positive emotions support attention, memory, participation, and communication, while anxiety, shame, boredom, and excessive pressure may prevent learners from using the language they already know. The paper offers practical suggestions for emotionally responsive FL teaching, including supportive feedback, predictable routines, playful repetition, cooperative tasks, and age-appropriate assessment.